Association between joint physical activity and healthy dietary patterns and hypertension in US adults: cross-sectional NHANES study - Yanzhou Zhu; Zhigang Wang (BMC Public Health, 2024)
Abstract Background Lack of physical activity (PA), poor dietary habits, or other unhealthy lifestyle behaviors are potential modifiable risk factors for hypertension. It has been sufficiently demonstrated in previous studies that physical activity or healthy dietary patterns can reduce the risk of hypertension. However, no research focused on the joint effects of PA and healthy dietary patterns on hypertension in a representative sample of adults. Methods We used data collected from the 2007–2018 National Health and Nutrition Examination Survey. Healthy dietary patterns were assessed with the Healthy Eating Index 2015 (HEI-2015), and PA was measured using the metabolic equivalent minutes per week reported in questionnaires. We created four lifestyle categories based on the HEI-2015 and PA: (1) unhealthy diet and physically inactive (less than recommended PA), (2) healthy diet but physically inactive, (3) unhealthy diet but physically active (recommended PA), (4) healthy diet and physically active. Logistic regression was used to evaluate the association between joint PA and HEI-2015 and hypertension. Results A total of 24,453 participants were enrolled in the study. Compared with unhealthy diet and physically inactive individuals, only healthy diet and physically active participants (adjusted odds ratio [AOR]: 0.77, 95% CI 0.65–0.9) were negatively associated with hypertension, while healthy diet but physically inactive participants (AOR: 0.89, 95% CI 0.76–1.03) and unhealthy diet but physically active participants (AOR: 0.9, 95% CI 0.76–1.06) were not associated with hypertension. Conclusion In a representative sample of US adults, our findings suggest that individuals with recommended PA and healthy dietary patterns have a lower risk of hypertension than those with an unhealthy diet or less than recommended PA. Healthy eating habits and regular PA are potential preventive precautions against hypertension.